2017
DOI: 10.1371/journal.pone.0190125
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus platform enhances transduction efficiency of human mesenchymal stem cells: An opportunity for cellular carriers of targeted TRAIL-based TR3 biologics in ovarian cancer

Abstract: Clinical application of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-based cancer therapeutics has not reached optimal potencies in part due to inadequate drug stability and inefficiencies in cancer-selective drug delivery. As such, innovative strategies regarding drug design and delivery are of utmost importance to achieve improved treatment results. With our current study, we aimed at exploring the groundwork for a two-stage targeting concept, which is based on the intrinsic tumor homing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Nonetheless, its use has been limited often by low stability and inefficient delivery in the tumor site [88]. Kuroki and colleagues used a TRAIL-based molecule called TR3 and transduced the TR3 expressing gene to ADSCs via an adenoviral vector [79]. Transduced ADSCs efficiently expressed TR3 and secreted it in the extracellular space.…”
Section: Adsc-mediated Expression Of Tumor-suppressing Molecules or Oncolytic Virusesmentioning
confidence: 99%
“…Nonetheless, its use has been limited often by low stability and inefficient delivery in the tumor site [88]. Kuroki and colleagues used a TRAIL-based molecule called TR3 and transduced the TR3 expressing gene to ADSCs via an adenoviral vector [79]. Transduced ADSCs efficiently expressed TR3 and secreted it in the extracellular space.…”
Section: Adsc-mediated Expression Of Tumor-suppressing Molecules or Oncolytic Virusesmentioning
confidence: 99%
“…Morrison et al were able to protect the vector from neutralizing antibodies and demonstrated significantly lower tumor load and absence of inflammatory toxicities by coating Ad5 with poly (hydroxypropyl methacrylamide (pHPMA) and retargeting to EGFR with EGF or cetuximab [151,152]. Thanks to their natural tumor tropism and immunomodulatory properties, mesenchymal stem cells (MSCs) of different origins have been used as carriers of oncolytic Ads [153][154][155], increasing targeted delivery and reducing the hepatic uptake and systemic toxicity seen in clinical trials of vectors such as Ad5-Δ24RGD [156]. Menstrual blood MSCs (MenSCs) were successfully used to deliver an Ad5/3Δ24 CRAd with microenvironment-responsive elements and the SPARC promoter without being blocked by antibodies present in the ascites, which also contain soluble factors that can serve as transcriptional enhancers [157].…”
Section: Overcoming Physical Barriers To Dissemination Of Oncolytic Amentioning
confidence: 99%
“…Among the most widely used viral vectors, lentivirus and adeno-associated virus (AAV) are preferred for human gene therapy applications, but adenovirus (AV) has important advantages as a research tool 17,18 . AV has the highest transduction efficiency in diverse target cells 16,19,20 ; unlike lentivirus, its genome does not integrate into the host genome, thus reducing off-target mutations; and AV has a substantially higher genome capacity than AAV 21 . We have used this capacity to co-package three CRISPR-Cas9 components along with their promoters: Cas9, sgRNA and a fluorescent protein to aid in sorting for transduced cells.…”
Section: Introductionmentioning
confidence: 99%